2008
DOI: 10.1088/0957-4484/19/43/435102
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt nanoparticles coated with graphitic shells as localized radio frequency absorbers for cancer therapy

Abstract: Graphitic carbon-coated ferromagnetic cobalt nanoparticles (C-Co-NPs) with diameters of around 7 nm and cubic crystalline structures were synthesized by catalytic chemical vapor deposition. X-ray diffraction and x-ray photoelectron spectroscopy analysis indicated that the cobalt nanoparticles inside the carbon shells were preserved in the metallic state. Fluorescence microscopy images and Raman spectroscopy revealed effective penetrations of the C-Co-NPs through the cellular plasma membrane of the cultured HeL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 29 publications
1
74
0
1
Order By: Relevance
“…Xu et al studied hyperthermia with the assistance of cobalt nanoparticles, although they did not apply an alternating magnetic field. This research group heated the particles by ultrasonic sound (350 kHz) and showed that the effects of the nanoparticles in vitro depended on the exposure time and the nanoparticle concentration [75] . However, as Rodriguez-Luccioni et al demonstrated in a comparative study, the viability of cells in vitro was affected significantly more by magnetic hyperthermia than by heating in a water bath, which implicates that magnetic hyperthermia might have additional effects on tumor cell viability [76] .…”
Section: Types Of Hyperthermiamentioning
confidence: 99%
“…Xu et al studied hyperthermia with the assistance of cobalt nanoparticles, although they did not apply an alternating magnetic field. This research group heated the particles by ultrasonic sound (350 kHz) and showed that the effects of the nanoparticles in vitro depended on the exposure time and the nanoparticle concentration [75] . However, as Rodriguez-Luccioni et al demonstrated in a comparative study, the viability of cells in vitro was affected significantly more by magnetic hyperthermia than by heating in a water bath, which implicates that magnetic hyperthermia might have additional effects on tumor cell viability [76] .…”
Section: Types Of Hyperthermiamentioning
confidence: 99%
“…Metal oxide [17, 66 -70] , metallic, mainly Fe and Co [71 -73] , and bimetallic, such as FePt [74,75] MNPs have been proposed for this purpose. Many of these materials were coated, to provide an inert and biologically compatible outer shell made of silica [67] , gold [43,57,76] or carbon [71,73] . [36,48] .…”
Section: Biomedicalmentioning
confidence: 99%
“…Intriguing potential applications of carbon-coated magnetic nanoparticle systems are emerging, such as the magnetic memory devices, drug delivery, and tumor therapy. [17][18][19] In this paper, we report the results on the preparation of cobalt nanoparticles using PLAL technique at room temperature, with the metal cobalt target immersed in toluene. Without the addition of surfactants, cobalt nanoparticles with graphitic carbon coating were produced.…”
Section: Introductionmentioning
confidence: 99%